Interrogating a cosmopolitanism of African higher education - Manthalu, C.H.; Waghid, Y. (South African Journal of Higher Education, 2019)
The immensity and inevitability of global interconnectedness have necessitated higher education to be cosmopolitan in its epistemological, and skills and attitudes development scope. Much has been written about the urgency, necessity and proposed modes of cosmopolitan higher education in Africa responsive to modern day demands and challenges. However, there is an outstanding need to interrogate the ontological assumptions and subsequent normative implications of the cosmopolitanism that informs African higher education. This paper argues that the globally predominant cosmopolitanism that also informs and is being pursued by African higher education is normatively problematic because it is exclusively grounded only in commonalities of the diverse people of the world, regarding their individuating differences as morally arbitrary and inhibitive of a realisation of cosmopolitan aspirations. Using Seyla Benhabib’s (1992) difference-grounded moral universalism, the paper argues that difference is constitutive of being a concrete individual or collectivity. As such African higher education ought to, as a matter of normative necessity, centre the subjectivities of the African experience. The central claims of this paper have implications on endeavors of re-imagining curriculum design, curriculum content selection and pedagogy in African higher education.